2023
DOI: 10.1002/cre2.714
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time evaluation of the biocompatibility of calcium silicate‐based endodontic cements: An in vitro study

Abstract: Introduction An ideal filling material should hermetically seal the communication pathways between the canal system and surrounding tissues. Therefore, during the last few years, the development of obturation materials and techniques to create optimal conditions for the proper healing of apical tissues has been a focus of interest. The effects of calcium silicate‐based cements (CSCs) on periodontal ligament cells have been investigated, and promising results have been obtained. To date, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…Although dental pulp stem cells and PDLSCs belong to the same mesenchymal stem cell lineage, they show differences in proteomics under osteogenic conditions [ 35 ]; they exhibit differences in the orientation of the sheet and stem cell markers as well [ 36 ]. CSCs used for root-end filling stimulate growth and proliferation of the PDLSCs, leading to improved healing and better tooth prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although dental pulp stem cells and PDLSCs belong to the same mesenchymal stem cell lineage, they show differences in proteomics under osteogenic conditions [ 35 ]; they exhibit differences in the orientation of the sheet and stem cell markers as well [ 36 ]. CSCs used for root-end filling stimulate growth and proliferation of the PDLSCs, leading to improved healing and better tooth prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine is an endodontic sealer composed of calcium silicate, primarily tricalcium silicate, with certain additives and a zirconium oxide radiopacifier. It is specifically designed to be utilized as a dentine replacement material and has undergone extensive scientific engineering (15).…”
Section: Methodsmentioning
confidence: 99%
“…Eluents of cements obtained from powder (20 mg/mL, three days) decreased cell proliferation [4,22], while other studies observed no changes in the growth rates when cells were treated with eluent from discs [0.14 mg/mL, four days]. Furthermore, cell proliferation rates exhibited distinct patterns when exposed to different dimensions of the material; for instance, a 4 × 3 mm disc led to decreased cell proliferation on the fifth day [19], whereas a 5 × 3 mm disc resulted in increased cell proliferation on the seventh day [9]. Another study reported increased proliferation when cells were grown directly on the surface of the material [29].…”
Section: Introductionmentioning
confidence: 92%
“…In this method, there are no specifications governing the variables involved in production of the eluents. The material can be shaped as discs [11,18,19] or crushed into powder [6,[20][21][22]. Likewise, the elution period varied across studies.…”
Section: Introductionmentioning
confidence: 99%